The Big Sick - Nanjiani, Kumail; Kazan, Zoe; Hunter, Holly; Romano, Ray; Kher, Anupam; Shroff, Zenobia; Akhtar, Adeel; Burnham, Bo; Bryant, Aidy; Braunohler, Kurt
A Pakistani-American stand-up comedian falls for a white grad student, and decides to keep their uncertain romance a secret from his traditionalist, Muslim family. However, their relationship gets more serious when she develops a mysterious illness, which in turn forces him to bond with her parents.
Streaming video file.